Peningkatan Kualitas Pembelajaran Kepada Anak Selama Pandemi Bidang Kesehatan Dan Pendidikan - Manurung, Miftah Aulia (AL-HANIF: Jurnal Pendidikan Anak dan Parenting, 2021)
Deli Serdang Regency is one of 33 (thirty three) Regencies/Cities currently in North Sumatra Province. Based on its geographical location, Deli Serdang Regency is located in the East Coast of North Sumatra which interacts directly with the Malacca Strait. Geographically, Deli. Serdang Regency is located at coordinates 2 o 57'' to 3 o 16'' North Latitude, and 98o 33'' to 99 o 27'' East Longitude. Administratively, Deli Serdang Regency consists of 22 (Twenty Two) Sub-districts, 14 Kelurahan and 380 Villages, with an area of 249,772 Ha (2,497.72 Km2). The sub-district with the largest area is Hamparan Perak District, which is 23,015 ha or 9.21% of the total area of Deli Serdang Regency. Meanwhile, the sub-district that has the smallest area is Deli Tua District, which is only 936 ha or 0.37% of the Deli Serdang Regency area.